Combinatory approach of methacrylated alginate and acid monomers for concrete applications. (2nd January 2017) - Mignon, Arn; Devisscher, Dries; Graulus, Geert-Jan; Stubbe, Birgit; Martins, José; Dubruel, Peter; De Belie, Nele; Van Vlierberghe, Sandra
Highlights: ⿢ Methacrylated alginate with two acrylic monomers were successfully synthesized. ⿢ A moisture uptake capacity of 110% of its weight is found at 95% relative humidity. ⿢ Swelling capacities up to 246 times its own weight is reached. ⿢ Alginate combined with acrylic acid has a very limited effect on mortar strength. ⿢ These materials can be interesting for self-healing applications in concrete. Abstract: Polysaccharides, and especially alginate, can be useful for self-healing of cracks in concrete. Instead of weak electrostatic bonds present within calcium alginate, covalent bonds, by methacrylation of the polysaccharides, will result in mechanically stronger superabsorbent polymers (SAPs). These methacrylated alginate chains as backbone are combined with two acrylic monomers in a varying molar fraction. These SAPs show a moisture uptake capacity up to 110% their own weight at a relative humidity of 95%, with a negligible hysteresis. The swelling capacity increased (up to 246 times its own weight) with a decreasing acrylic acid/2 acrylamido-2-methylpropane sulfonic acid ratio. The SAPs also showed a thermal stability up to 200 °C. Interestingly, the SAP composed of alginate and acrylic acid exerted a very limited decrease in compressive strength (up to 7% with addition of 1 wt% SAP) rendering this material interesting for the envisaged self-healing application.